Spectrum of renal vascular lesions among patients with lupus nephritis: An experience from a tertiary care center - Madhumita Paul; Soma Addya; Moumita Sengupta; Keya Basu; Arpita Roychowdhury; Manimoy Bandopadhyay (Wolters Kluwer Medknow Publications, 2023)
Background: Lupus nephritis (LN) is the assemblage of glomerular, tubulointerstitial and vascular changes. Despite the fact that glomerular changes are overemphasized in pathological classification and scoring system, but the existence of vascular damage negatively impact the clinical course. Aims and Objective: This study was conducted to determine the clinicopathological spectrum of renal vascular lesions in lupus nephritis. Materials and Methods: Renal microvascular lesions in biopsy proven lupus nephritis were classified into 5 major categories-thrombotic microangiopathy, true vasculitis; lupus vasculopathy, uncomplicated vascular immune deposits, and arterial. Clinical details, laboratory parameters and histopathological variables were compared among all groups. Summary of chronic changes was also assessed. Results: Biopsies from 56 patients revealed thrombotic microangiopathy (2), lupus vasculopathy (3), uncomplicated vascular immune deposit (6), PAN type vasculitis (1) and arterial sclerosis (13). No renal vascular lesions were found in 35.18% of patients. At the time of biopsy, arterial sclerosis or lupus vasculopathy patients were older Nephritis subtype. Activity indices were higher in lupus vasculopathy group whereas patients with arteriosclerosis showed highest chronicity index. Conclusions: Renal vascular lesions are common in systemic lupus erythematosus patients with nephritis and may be associated with aggressive clinical course.